2004
DOI: 10.1016/j.cub.2004.05.044
|View full text |Cite
|
Sign up to set email alerts
|

A Barrier to Lateral Diffusion in the Cleavage Furrow of Dividing Mammalian Cells

Abstract: Barriers to diffusion of proteins and lipids play an important role in generating functionally specialized regions of the plasma membrane. Such barriers have been reported at the base of axons, at the bud neck in Saccharomyces cerevisiae, as well as at the tight junctions of epithelia. How diffusion barriers are formed and how they effect behavior of both inner and outer leaflets of the bilayer are not fully understood. Here, we provide evidence for a cortical barrier to diffusion within the cleavage furrow of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
85
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(95 citation statements)
references
References 26 publications
9
85
0
1
Order By: Relevance
“…Diffusion barriers have been previously identified in cleavage furrows (Schmidt and Nichols, 2004) and in the leading edge of cellular protrusions (Weisswange et al, 2005). Whereas those structures result from larger changes in cell morphology, macropinocytic circular ruffles are self-organized.…”
Section: Discussionmentioning
confidence: 97%
“…Diffusion barriers have been previously identified in cleavage furrows (Schmidt and Nichols, 2004) and in the leading edge of cellular protrusions (Weisswange et al, 2005). Whereas those structures result from larger changes in cell morphology, macropinocytic circular ruffles are self-organized.…”
Section: Discussionmentioning
confidence: 97%
“…The establishment of compartments around the cortical Factin/Myosin 2 array appears to be a conserved feature of furrowing during conventional cytokinesis, common from yeast (Dobbelaere and Barral, 2004;Takeda et al, 2004;Wachtler et al, 2003), to sea urchin and Xenopus embryos (Byers and Armstrong, 1986), to cultured mammalian cells (Schmidt and Nichols, 2004). Previous analyses in cellularizing Drosophila embryos similarly suggested that the F-actin/Myosin 2 furrow canals are discrete compartments that form at the tips of incipient furrows and are maintained as the furrows ingress (Lecuit and Wieschaus, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…This compartmentalization function appears to be conserved in fission yeast, where a double ring of septin filaments encompasses the contractile apparatus and provides for efficient dissolution of the primary septum [32,33]. It appears that septins might have a similar role in mammalian cells because septins are prominent components of the cleavage furrow and a diffusion barrier within the cleavage furrow has been demonstrated [34].…”
Section: Septin Functionsmentioning
confidence: 99%